Economic Benefits of Sponsored Clinical Trials in Cancer for the Colombian Healthcare System: A Real‐World Evidence Approach - Leonardo Rojas; Natalia Sánchez; Jorge Ceballos; Antonio Robles; Carlos A. Badillo; Virginia Abello; Carlos Bonilla; William A. Mantilla; Jairo Zuluaga; Gilberto Lopes; Oscar Arrieta; Andrés F. Cardona (Cancer Medicine)
ABSTRACT Purpose Clinical trials (CTs) are essential for the research and development of new cancer treatment technologies. Evaluating their economic impact and the potential cost savings for healthcare systems in low‐ and middle‐income countries is crucial for informing healthcare policy and decision‐making. This study estimates the economic benefits to the Colombian healthcare system from the inclusion of hematology and oncology patients in sponsored CTs. Methods This study utilized real‐world data from the Luis Carlos Sarmiento Angulo Cancer Treatment and Research Centre (CTIC), a comprehensive cancer center in Bogotá, Colombia. Tumor types were selected based on their prevalence and economic burden. A Budget Impact Analysis was conducted following the methodology of the local Health Technology Assessment Agency, using data from five prioritized tumor types. Clinical data and associated costs were extracted from the institutional data lake, and cost‐generating events for each disease were validated by CTIC clinical experts. The estimated eligible population for phase 3 CTs was derived from literature reviews and expert opinions from CTIC clinicians. Prevalent and incident population data were obtained from the Colombian High‐Cost Account. Results A total of 7703 potential patients were eligible for inclusion in the CTs, with an associated healthcare cost of USD 244,151,552 by 2023 (1 USD = 4325 COP). If at least 20% of these patients participated in CTs by 2023, the projected annual cost savings would be USD 48,830,310. Among the evaluated cancers, advanced prostate cancer incurred the highest costs due to its high prevalence and potential for inclusion in CTs. Conclusion Over 5 years, potential cost savings could range from USD 244 million (assuming a 20% enrolment rate) to 1.22 billion (with 100% enrolment), alleviating financial pressures on the Colombian healthcare system. These savings would contribute to the system's long‐term financial sustainability while ensuring timely access to innovative cancer treatments.